Improving the swelling capacity of granular cold-water rice starch by ultrasound-assisted alcoholic-alkaline treatment - Kannika Kunyanee; Kanyarak Phadtaisong; Jutarat Na Chiangmai; Natch Parittapongsachai; Tai Van Ngo; Naphatrapi Luangsakul; Sirada Sungsinchai (My University, 2023)
The aim of this study was to determine the ability to improve the capacity of cold swelling and cold-water solubility of rice starch by ultrasonic-assisted alcohol-alkaline and alcohol-alkaline methods. To achieve this, ultrasound powers (U) were varied (30%, 70%, 100%) under the granular cold-water swelling starch (GCWSS) preparation (GCWSS + 30 %U, GCWSS + 70 %U, and GCWSS + 100 %U). The effects of these methods on morphological, pasting properties, amylose content, ratio of 1047/1022 spectra by FTIR, turbidity, freeze-thaw stability, and gel texture were also studied and compared. The results showed that the surface of GCWSS granules presented a honeycomb especially GCWSS + U treatments exhibited more porous on the surface of starch granules. The cold swelling power and solubility of GCWSS + U samples were increased which confirmed by reducing ratio of ordered structure to amorphous structure of starch, and turbidity was also decreased. Moreover, pasting temperature, breakdown, final viscosity, and setback decreased while peak viscosity increased as measured using a Rapid Visco Analyzer. The freeze-thaw stability of GCWSS + U was more resistant to syneresis than GCWSS under repeated freeze-thaw cycles. The reduction of gel hardness and springiness was observed using Texture Analyzer. These changes were enhanced with increasing ultrasound powers. Thus, the results indicate that the different ultrasound-assisted alcohol-alkaline treatments for preparing GCWSS show an effective use in the preparation of GCWSS with improved cold-water swelling and reduced retrogradation of rice starch.
Keywords: Syneresis; Retrogradation (starch); Swelling capacity; Food composition and properties